2020
DOI: 10.1108/jabes-04-2020-0036
|View full text |Cite
|
Sign up to set email alerts
|

Board governance quality and risk disclosure compliance among financial institutions in Uganda

Abstract: PurposeThis paper aims to examine the impact of board governance quality (BGQ) and its mechanisms, namely board activity, board independence, board communication and board expertise, on the level of risk disclosure compliance (RDC) among financial institutions (FIs) in Uganda.Design/methodology/approachThe study adopts a cross-sectional design where data are collected through a questionnaire survey and audited financial statements of 83 FIs. The authors employ partial least square structural equation modeling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 55 publications
0
11
2
Order By: Relevance
“…Equally, leverage was found to be a positive determinant of RD (Tauringana and Chithambo, 2016;Muturi, 2018) contrary to the finding of Dobler et al (2011), Aryani and Hussainey (2017) and Netti (2019). Regarding board-related attributes, Carmona et al (2016), Elshandidy and Neri (2015) and Nkuutu et al (2020) found a positive association between board size and RD, whilst Elzahar and Hussainey (2012), Allini et al (2016) and Khandelwal et al (2020) reported no association. Likewise, board independence positively influences RD (Abraham and Cox, 2007;Khandelwal et al, 2020), whilst Saggar and Singh (2017) and Ibrahim et al (2019) found no association.…”
Section: Introductioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Equally, leverage was found to be a positive determinant of RD (Tauringana and Chithambo, 2016;Muturi, 2018) contrary to the finding of Dobler et al (2011), Aryani and Hussainey (2017) and Netti (2019). Regarding board-related attributes, Carmona et al (2016), Elshandidy and Neri (2015) and Nkuutu et al (2020) found a positive association between board size and RD, whilst Elzahar and Hussainey (2012), Allini et al (2016) and Khandelwal et al (2020) reported no association. Likewise, board independence positively influences RD (Abraham and Cox, 2007;Khandelwal et al, 2020), whilst Saggar and Singh (2017) and Ibrahim et al (2019) found no association.…”
Section: Introductioncontrasting
confidence: 66%
“…The mean (median) RDI score is 41.2% (32.1%) with a standard deviation of 14.8% at the overall level. The mean value is comparable to 40%, 41.6% and 52.9% in Malawi, MENA and Uganda, respectively (Tauringana and Chithambo, 2016; Elamer et al , 2019; Nkuutu et al , 2020). However, the mean is considered low compared to prior studies (Linsley and Shrives, 2006; Miihkinen, 2012).…”
Section: Resultsmentioning
confidence: 56%
“…Smaller boards are better able to closely monitor management, the dual role of CEOs is likely to improve bank performance, and the presence of blockholders in the ownership structure tends to have a positive effect on the performance of the Islamic banking sector (Naushad & Malik, 2015 ). Simultaneously, the recent literature is still focusing on the governance in the financial context and most findings in this direction confirm that efficiency represents one of the main sources of efficiency and performance (Bourakba, 2014 ; Mollah & Zaman, 2015 ; Farag et al, 2018 and Safiullah & Shamsuddin, 2019 ; Ngo et al, 2019 ; Nkuutu et al, 2020 ; Shahid et al, 2020 ). Governance is therefore a strong determinant of banking efficiency.…”
Section: Previous Researchmentioning
confidence: 88%
“…In fact, the impact of gender diversity on bank profitability and bank stability is still ambiguous (García-Meca et al, 2014). While a number of studies suggest a positive relationship between gender diversity and a well-functioning board that contributes to the organization success (Ward, Wylie & Hamill, 2011), the contributions of women leaders are being challenged under some certain circumstances (Adams & Ferreira, 2009, Sumbul Sajjad, 2015, such as the time period of the studies, countries, economic environment, regulatory and governance structures, culture, and size of capital markets (Rhode & Packel, 2014;Nkuutu et. al, 2020).…”
Section: Introductionmentioning
confidence: 99%